Degree of Awareness and Food Safety and Health Consciousness; The Impact on Confidence Towards MUI's Halal Logo (an Evidence from Bandung) - Mahiranissa, Aulia; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract. Indonesia in majority is inhabited by muslim religious communities. Almost all aspects of the society associated with Islam rules as a basic guideline. Islam preaches a systematic way of life. One of the standards is the concept of Halal. An Arabic word which means lawful or permitted for muslims. The existence of food composition awareness and some issues stated the widespread use of ingredients that are not healthy, has triggered Indonesian people to be more careful and rely on Halal logo which guarantees healthy food besides for obeying Islamic rule. With the growing issue regarding the issues, the presence of Halal logo becomes a factor that is able to support the consumer on their purchasing process. The study was then conducted with the aim of mapping the detail of factors that is able to make consumers believe in the Halal logo. Further to enrich the study, the research will also give an idea of what kind of consumers that have paid more attention to their use of the Halal logo on food and beverage products. With the Halal logo mapping and research on the types of consumer who has a special concern towards Halal logo, researcher hopes that this study can be the base insight about the implementation of the Halal logo by food manufacturers. This knowledge is expected to drive the muslim society in Indonesia to gain their confidence towards MUI’s Halal logo anad able to make them feel safer when they buy food ad beverage products in Indonesia. Keywords: Key word: MUI’s Halal logo, confidence, consumer, food and beverage, factor analysis.